Design, analysis and fabrication of wire cutting machine / Muhammad Nabil Saeman and Abdul Hadi Abdol Rahim @ Ibrahim - Saeman, Muhammad Nabil; Rahim @ Ibrahim, Abdul Hadi Abdol (School of Mechanical Engineering, 2022)
Nowadays, most people out there use manual wire cutters to cut wires and use more energy than the automatic wire cutter. Using the manual cutter for a long time, the probability for hand injuries is much higher. This project basically gave an initial theme on how we can approach to solve this kind of problem. In addition to that, a designated automatic wire machine is created which gives more accuracy and reduces the human error, manpower, reliable work done, and saves the wastage of wire. This product can help reduce the time of cutting wires and produce better results. Basically, the function of this wire cutting machine is the same with the manual wire cutter but with different features. Users must put input of number of wires and length of wires that need to be cut. This automatic machine is fully using an electric supply and has microprocessors. It features an LCD display for setup and its operation. Other than that, this machine uses a stepper and servo motor to pull and cut the wire. In conclusion, this wire cutting machine is a time saving product because it can save time from measuring and cutting wires. It also reduces the risk of hand injuries to the user